2014
DOI: 10.1117/1.jmi.1.3.031005
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization-prepared rapid acquisition with gradient echo magnetic resonance imaging signal and texture features for the prediction of mild cognitive impairment to Alzheimer’s disease progression

Abstract: Abstract. Early diagnoses of Alzheimer's disease (AD) would confer many benefits. Several biomarkers have been proposed to achieve such a task, where features extracted from magnetic resonance imaging (MRI) have played an important role. However, studies have focused exclusively on morphological characteristics. This study aims to determine whether features relating to the signal and texture of the image could predict mild cognitive impairment (MCI) to AD progression. Clinical, biological, and positron emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…It is also noted that are very few studies [30], [129] that combine volume, thickness, shape, intensity, and texture in multivariate assessment of the disease, which in turn may result to better classification and prediction accuracies. Martinez Torteya et al [80] used images from the ADNI database with their corresponding segmentation masks, provided by [147], to establish ROIs for every image. For each ROI they used 9 texture-related features together with 13 morphometrical features and 28 signal distribution related features.…”
Section: Future Workmentioning
confidence: 99%
“…It is also noted that are very few studies [30], [129] that combine volume, thickness, shape, intensity, and texture in multivariate assessment of the disease, which in turn may result to better classification and prediction accuracies. Martinez Torteya et al [80] used images from the ADNI database with their corresponding segmentation masks, provided by [147], to establish ROIs for every image. For each ROI they used 9 texture-related features together with 13 morphometrical features and 28 signal distribution related features.…”
Section: Future Workmentioning
confidence: 99%
“…Its in luence in declarative memory is patent, and many studies have reported atrophy in early AD, along with surrounding structures such as the amygdala and the parahippocampal gyrus. Most studies report early neurodegeneration in MCI in these structures and generally in the temporal lobe [27,8,35,22]. Martinez-Torteya et al [22] also reported the left medial orbital gyrus and the left inferiolateral remainder of the parietal lobe (area between inferior parietal gyrus and the supramarginal gyrus).…”
Section: Dmentioning
confidence: 99%
“…Neuroimaging, with its ability to perform in vivo exploration of brain structure and function, could be a key source of information to enhance MCI diagnosis. Many works have explored the possibility of multivariate analyses of structural and functional imaging using techniques such as Principal Component Analysis [14,28], Support Vector Machines [24,16,10], texture analysis [35,22,19] or volume and shape analysis [5,23,27,26,6,8]. These works used semiautomatic methodology to segment and extract features from images that leaded to higher discriminative Computer Aided Diagnosis (CAD) systems [18], offering performances up to 80% in the diagnosis of MCI.…”
Section: Imentioning
confidence: 99%
“…From our experience [32,34], first-and second-order statistical features can summarize the behavior of different types of natural signals [6] that can be used to develop ILE systems; additionally, other types of problems with several approaches have been tackled with statistical features [35][36][37]. Therefore, the 16 statistical features listed in Table 4 were extracted from each sample of the human activities done in each selected room.…”
Section: Feature Extractionmentioning
confidence: 99%